2005
DOI: 10.2337/diacare.28.11.2728
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pitavastatin on Urinary Liver-Type Fatty Acid–Binding Protein Levels in Patients With Early Diabetic Nephropathy

Abstract: OBJECTIVE -Liver-type fatty acid-binding protein (L-FABP) is expressed in renal proximal tubules and is reported to be a useful marker for progression of chronic glomerulonephritis. The aim of this study was to determine whether urinary L-FABP levels are altered at various stages of diabetic nephropathy and whether pitavastatin affects urinary L-FABP levels in early diabetic nephropathy.RESEARCH DESIGN AND METHODS -Fifty-eight patients with type 2 diabetes (34 men and 24 women, median age 52 years) and 20 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
92
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 20 publications
3
92
1
Order By: Relevance
“…8,9 Urinary liver-type fatty acid-binding protein (L-FABP) is an important marker of tubulointerstitial changes in diabetic nephropathy, whereas oxidative stress is a pathogenetic factor underlying diabetes complications such as nephropathy. 10 For this reason, 8-hydroxy-2¢-deoxyguanosine (8-OHdG) has been reported to serve as a sensitive biomarker of oxidative DNA damage in vivo, demonstrating significantly increased urinary excretion levels with severe tubulointerstitial damage. 11,12 In addition, aldosterone induces oxidative stress in vascular cells through NADPH oxidase activation, which has a central role in endothelial dysfunction and atherosclerotic vascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Urinary liver-type fatty acid-binding protein (L-FABP) is an important marker of tubulointerstitial changes in diabetic nephropathy, whereas oxidative stress is a pathogenetic factor underlying diabetes complications such as nephropathy. 10 For this reason, 8-hydroxy-2¢-deoxyguanosine (8-OHdG) has been reported to serve as a sensitive biomarker of oxidative DNA damage in vivo, demonstrating significantly increased urinary excretion levels with severe tubulointerstitial damage. 11,12 In addition, aldosterone induces oxidative stress in vascular cells through NADPH oxidase activation, which has a central role in endothelial dysfunction and atherosclerotic vascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary excretion of L-FABP increases with the deterioration of kidney function and is a useful clinical marker for monitoring chronic kidney disease [3]. We have reported that urinary L-FABP may be a useful clinical marker for type 2 diabetic nephropathy [4].…”
mentioning
confidence: 99%
“…Urinary excretion of L-FABP increases with the deterioration of kidney function and is a useful clinical marker for monitoring chronic kidney disease [3]. We have reported that urinary L-FABP may be a useful clinical marker for type 2 diabetic nephropathy [4].Several treatments have been shown to halt or retard the progression of diabetic nephropathy. Suppression of the renin-angiotensin system is currently the most widely used therapy in clinical practice [2].…”
mentioning
confidence: 99%
See 2 more Smart Citations